Projeto Vida no Vale: universal access to water and sanitation in the North East of Minas Gerais (Brazil) - Kauark-Leite, L.; Vinçon-Leite, B.; Deroubaix, J.F.; Loireau, A.; Silveira, D.; Haddad, E. (Hydrology and Earth System Sciences Discussions, 2007)
In the rural areas of the developing countries, the access to water supply and sanitation services is still largely inadequate. Poor governance of the water sector is frequently singled out as a cause and reforms are required. Studies analyzing the great diversity of restructuring efforts currently being undertaken in the water sector have not succeeded in determining the most appropriate institutional and economic framework for such reforms. Moreover they underline the lack of documentation on actual projects and call for concrete models and tools for improving water and sanitation services (WSS) and for adapting water utility practice to real conditions. In this context, the Vida no Vale (Life in the Valley) project is aimed at bringing universal access to WSS for all inhabitants of both urban and rural areas, in the north-eastern area of the Brazilian State of Minas Gerais. The project takes sustainable development as its guiding principle, and relies on the joint implementation of an innovative technical design, a governance model involving public participation and subsidiarity, and an economic structure combining financial viability and social equity. Designed at a consistent geographical and hydrological scale, it includes the creation of a regional subsidiary of the existing state water company as a keystone element. The institutional organisation also relies on the creation of a public board consisting of the 92 municipalities of the project region and of the State of Minas Gerais. This board will be in charge of the system’s governance. The paper will present the first step of the project (2006), consisting of a feasibility study and the implementation of 9 pilot sub-projects. During the feasibility study, the supply, demand and capacity to pay for water services were defined, existing infrastructure appraised, the necessary amount of investment assessed and an innovative operational model and a sustainable management system, including civil society participation, defined. The main features of the Vida no Vale project have been tested in 9 pilot sub-projects, and implemented in municipalities chosen for their low Human Development Index and for the lack of WSS, in both urban and rural areas. A second phase corresponding to the project’s final implementation will run from 2007 to 2011. The ongoing successful accomplishment of the Vida no Vale project would make it an exemplary and replicable model for other poor regions.